2008
DOI: 10.1176/appi.ajp.2007.07101581
|View full text |Cite
|
Sign up to set email alerts
|

Increased Anxiety During Anticipation of Unpredictable But Not Predictable Aversive Stimuli as a Psychophysiologic Marker of Panic Disorder

Abstract: Objective-Predictability is a fundamental modulator of anxiety in that the ability to predict aversive events mitigates anxious responses. In panic disorder, persistent symptoms of anxiety are caused by anticipation of the next uncued (unpredictable) panic attack. The authors tested the hypothesis that elevated anxious reactivity, specifically toward unpredictable aversive events, is a psychophysiological correlate of panic disorder.Method-Participants were exposed to one condition in which predictable aversiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
316
7
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 278 publications
(353 citation statements)
references
References 41 publications
29
316
7
1
Order By: Relevance
“…The NPU task manipulates uncertainty regarding both IF (shock probability) and WHEN (shock timing) shocks will occur. The NPU task has been used to examine drug administration and deprivation effects on negative affective response 4,34 and etiological mechanisms in mood and anxiety disorders [22][23][24][41][42][43] . In other research, Curtin and colleagues have also developed variants of these cued threat tasks that precisely manipulate threat uncertainty about WHEN (shock timing) 5,29,44 ; WHERE (administration location on body for shock) 25 ; and HOW BAD (shock intensity) 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NPU task manipulates uncertainty regarding both IF (shock probability) and WHEN (shock timing) shocks will occur. The NPU task has been used to examine drug administration and deprivation effects on negative affective response 4,34 and etiological mechanisms in mood and anxiety disorders [22][23][24][41][42][43] . In other research, Curtin and colleagues have also developed variants of these cued threat tasks that precisely manipulate threat uncertainty about WHEN (shock timing) 5,29,44 ; WHERE (administration location on body for shock) 25 ; and HOW BAD (shock intensity) 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In the Unpredictable condition of the NPU task, shocks are fully unpredictable. Patients with posttraumatic stress and panic disorders exhibit selectively increased startle potentiation during unpredictable but not predictable shock in the NPU task 22,23 . In other work, medications prescribed to treat anxiety have a greater effect on startle potentiation during unpredictable shock than during predictable shock in the NPU task 24 .…”
Section: Translational Research With Animals Using the Startle Responsementioning
confidence: 98%
“…In this regard, other findings by Grillon et al (2009b) are also relevant. In particular, they observed that startle potentiation to short-duration stimuli that have been paired with shock are no greater in post-traumatic stress (Grillon et al, 2009b) and panic disorder patients (Grillon et al, 2008) than in healthy controls, but that the startle responses that occur between stimulus presentations, which as noted earlier may reflect a more sustained type of anxiety to the less-predictive threat context, are greater (cf, Davis et al, 2010). These very interesting results lend support to the view that drugs that reduce sustained startle increases may be more clinically efficacious than those that preferentially reduce phasic startle increases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, evidence from developmental, neurobiological, and pharmacological preclinical studies suggests that contextual conditioning and explicit cue conditioning constitute distinct processes mediated by separate brain systems (Ameli et al, 2001;Luyten, Casteels, Vansteenwegen, van Kuyck, Koole, Van Laere et al, 2011). For comprehensive reviews, see Anagnostaras, Gale, and Fanselow (2001); Davis (1998) ;Gewirtz, McNish, and Davis (2000); Grillon (2002);and Grillon, Lissek, Rabin, McDowell, Dvir and Pine (2008).…”
Section: Contextual Conditioningmentioning
confidence: 99%